Peningkatan Kualitas Tata Kelola dalam Pengelolaan Dana Desa di Desa Buaran Bambu Kabupaten Tangerang - Aldi, Aldi; Santoso, Seno; Prasetyo, Eko (Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to explore ways to improve governance standards in Buaran Bambu Village, Tangerang Regency. The research methodology used is descriptive qualitative, and data were collected through observation, interviews, and documentation. As far as funding sources are concerned, the Village Fund Implementation Stage only has an accessible project board. Regarding accountability, the Buaran Bambu village government currently does not have a website that provides information on regional financial management. Meanwhile, the passive attitude of the community in directing and encouraging growth is an obstacle to improving governance standards in managing village funds in Buaran Bambu Village.